Repeated injury promotes tracheobronchial tissue stem cell attrition. (21st September 2021) - Ghosh, Moumita; Hill, Cynthia L.; Alsudayri, Alfahdah; Lallier, Scott W.; Hayes, Don; Wijeratne, Saranga; Tan, Zhang Hong; Chiang, Tendy; Mahoney, John E.; Carraro, Gianni; Stripp, Barry R.; Reynolds, Susan D.
Abstract: Chronic lung disease has been attributed to stem cell aging and/or exhaustion. We investigated these mechanisms using mouse and human tracheobronchial tissue‐specific stem cells (TSC). In mouse, chromatin labeling and flow cytometry demonstrated that naphthalene (NA) injury activated a subset of TSC. These activated TSC continued to proliferate after the epithelium was repaired and a clone study demonstrated that ~96% of activated TSC underwent terminal differentiation. Despite TSC attrition, epithelial repair after a second NA injury was normal. The second injury accelerated proliferation of previously activated TSC and a nucleotide‐label retention study indicated that the second injury recruited TSC that were quiescent during the first injury. These mouse studies indicate that (a) injury causes selective activation of the TSC pool; (b) activated TSC are predisposed to further proliferation; and (c) the activated state leads to terminal differentiation. In human TSC, repeated proliferation also led to terminal differentiation and depleted the TSC pool. A clone study identified long‐ and short‐lived TSC and showed that short‐lived TSC clones had significantly shorter telomeres than their long‐lived counterparts. The TSC pool was significantly depleted in dyskeratosis congenita donors, who harbor mutations in telomere biology genes. The remaining TSC had short telomeres and short lifespans. Collectively, the mouse and human studies support a model in which epithelial injury increases the biological age of the responding TSC. When applied to chronic lung disease, this model suggests that repeated injury accelerates the biological aging process resulting in abnormal repair and disease initiation. Abstract : Biological aging of tracheobronchial tissue specific stem cells (TSC) and their trophic unit, the pseudostratified conducting airway epithelium. Each injury activates a subset of TSC which proliferate and undergo terminal differentiation. Thus, each injury cycle depletes the TSC pool and many injuries compromise epithelial regeneration. Over time, biological age exceeds chronological age and increases the risk of chronic lung disease.